A New Compound Control for Mars Entry Guidance. Issue 3 (1st August 2018) - Shen, Ganghui; Xia, Yuanqing; Zhang, Lijun; Zhang, Jinhui; Cui, Bing
Abstract: In this paper, a novel compound control method consisting of adaptive finite-time sliding mode control (AFTSMC) law and final position guidance (FPG) is proposed to achieve high-precision guidance for Mars entry. In the first stage of entry, by employing adaptive law and extended state observer (ESO), an AFTSMC law is designed to avoid the overestimating control gains and then eliminate the chattering effectively. Furthermore, the proposed AFTSMC law not only provides strong robustness against uncertainties but also achieves finite-time convergence of tracking error. In the second stage, a new FPG is used to accurately deliver the vehicle to the required target in three-dimensional space. Therefore, the compound controller combines the advantages of AFTSMC law and FPG method, and numerical simulation results show that the proposed compound controller can not only provide favorable control performance but also improve the entry guidance precision under large uncertainties.